Genes, economics, and happiness - Jan-Emmanuel De Neve; James H. Fowler; Bruno S. Frey (Center for Economic Studies and ifo Institute (CESifo), 2010)
Research on happiness has produced valuable insights into the sources of subjective well-being. A major finding from this literature is that people exhibit a baseline happiness that shows persistent strength over time, and twin studies have shown that genes play a significant role in explaining the variance of baseline happiness between individuals. However, these studies have not identified which genes might be involved. This article presents evidence of a specific gene that predicts subjective well-being. Using data from the National Longitudinal Study of Adolescent Health, we show that individuals with a transcriptionally more efficient version of the serotonin transporter gene (5HTT) are significantly more likely to report higher levels of life satisfaction. Having one or two alleles of the more efficient type raises the average likelihood of being very satisfied with one's life by 8.5% and 17.3%, respectively. This result may help to explain the stable component of happiness and suggests that genetic association studies can help us to better understand individual heterogeneity in subjective well-being.
Keywords: A12; Z00; 330; happiness; subjective well-being; genetics; Lebenszufriedenheit; Gentechnik; USA